The Principal's Role as Manager and Teacher Pedagogic Competence in Online Learning - Nur Ngaziah; Umi Pratiwi; Siska Desy Fatmaryanti; Aulia Fakhrina; Rizky Fadjar Choirrul Linda (Universitas Pendidikan Ganesha, 2021)
The Covid-19 pandemic requires people to learn online, one of which is at the elementary school level. Principals must be able to play a role as managers in managing learning during the Covid-19 Pandemic. This study aims to analyze the role of the principal as a manager and the pedagogical competence of teachers in online learning during the Covid-19 period. This type of research is descriptive quantitative research, namely by interpreting the data obtained from the field. Data collection was carried out on 4 principals and 49 teachers using a questionnaire distributed via google forms. Data analysis used descriptive quantitative with percentages. The results showed that the principal's role as a manager in online learning was not optimal in the indicators of the school determining the curriculum used in online learning (44%) and the principal facilitating support for online learning (50%). At the same time, the pedagogic competence also showed less than optimal in Playing their competencies is shown by the 5 lowest percentage indicators, including understanding the cognitive development of students (59%), designing learning methods (52%), designing learning models (56%), carrying out assessments of learning outcomes (54.5%), and conducting material assessments. (56%). With a strong commitment from teachers and principals, various efforts and programs carried out during online learning will optimally achieve learning objectives.